2015
DOI: 10.1007/s11011-015-9665-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia in newly diagnosed patients with multiple sclerosis

Abstract: There are limited data regarding glucose metabolism dysregulation in multiple sclerosis (MS). Present study investigates glucose and insulin response during oral glucose tolerance test (oGTT) in MS patients. We examined 19 MS patients and 19 age, sex and body mass index (BMI) matched healthy controls. MS patients were newly diagnosed, untreated and with low Expanded Disability Status Scale (EDSS) score (1.1 ± 0.7). Plasma glucose, lactate, insulin and GLP-1 during oGTT, and fasting adipokines, lipid and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 39 publications
3
42
0
1
Order By: Relevance
“…Furthermore, through the secretion of adipokines, adipose tissue is strongly involved in the regulation of energy balance, insulin sensitization and immune response [33,34]. Among the adipokines, adiponectin, abundantly secreted in the serum, plays a significant role in autoimmune diseases although controversial results have been reported with regard to MS [22][23][24][25][26]. Very recently and in accordance with our results, the study of C ß oban et al [27] confirmed the involvement of adipokines in both the pathogenesis and progression of MS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, through the secretion of adipokines, adipose tissue is strongly involved in the regulation of energy balance, insulin sensitization and immune response [33,34]. Among the adipokines, adiponectin, abundantly secreted in the serum, plays a significant role in autoimmune diseases although controversial results have been reported with regard to MS [22][23][24][25][26]. Very recently and in accordance with our results, the study of C ß oban et al [27] confirmed the involvement of adipokines in both the pathogenesis and progression of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, different studies have characterized total adiponectin in MS with controversial results . Recently, Çoban et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly diagnosed MS patients exhibit hyperinsulinemia and decreased insulin sensitivity (Penesova et al, 2015) suggesting that obesity is a potential risk factor for MS (Palavra et al, 2016). Treating underlying metabolic syndrome with classic anti-diabetic drugs such as metformin and pioglitazone ameliorates metabolic disturbances, reduces MRI-evident lesion frequency and dampens T-cell pro-inflammatory response in MS patients (Negrotto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increased prevalence of insulin resistance and impaired glucose tolerance in MS patients was reported (Oliveira et al, 2014; Penesova et al, 2015; Wens et al, 2013). In previous studies, IL-17A inhibited adipogenesis and moderated adipose tissue accumulation in vitro and IL-17a −/− mice showed increased bodyweight, glucose tolerance and insulin sensitivity (Ahmed and Gaffen, 2010; Ahmed and Gaffen, 2013; Straus, 2013; Winer et al, 2009; Zuniga et al, 2010).…”
Section: Discussionmentioning
confidence: 99%